Effect of welding parameters on lap shear tensile properties of dissimilar friction stir spot welded AA 5754-H22/2024-T3 joints - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2013)
In this study, the effect of weld parameters on mechanical properties, such as lap shear fracture load, of friction stir spot welded dissimilar lap joints was studied. The effects of the plate positioning, the plunge depth and the dwell time as well as the tool tilt angle on the joint strength were investigated. The experimental results showed that the positioning of the sheets played an important role on the strength of the joints. The joint strength was higher when AA 5754 sheet is placed on the top, whereas lower strength values were displayed by dissimilar joints produced by placing AA 2024 as the upper sheet. It was also observed that the plunge depth, dwell time and tool tilt angle had a strong effect on the failure mode of the friction stir spot welded lap joints produced. The joints exhibited two different fracture modes, namely cross and pullout nugget under lap shear tensile testing conditions.
Keywords: Mechanical characterisation; Friction stir spot welding; Aluminium alloys; Failure; MECHANICAL-PROPERTIES; STATIC STRENGTH; FAILURE MODES; MICROSTRUCTURE; ALLOY; RESISTANCE; PROGRESS; LASER